2020
DOI: 10.1186/s12896-020-00642-x
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study of the production of metabolites from in vitro cultures of C. ensiformis

Abstract: Background Canavalia ensiformis is a legume native to Central and South America that has historically been a source of protein. Its main proteins, urease, and lectin have been extensively studied and are examples of bioactive compounds. In this work, the effect of pH and light effects on the growth of C. ensiformis were analyzed. Also, the bioactive compounds such as phenols, carotenoids, chlorophyll a/b, and the growth of callus biomass of C. ensiformis from the effect of different types of light treatments (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 66 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…Recent report by Hassanpour [34] found that red-blue LED treatment was beneficial for callus production and secondary metabolism in Hyoscyamus reticulatus. Similarly, the maximum callogenic biomass and high concentrations of bioactive compounds in Canavalia ensiformis were reported in mixed red-blue light treatment [35]. Moreover, white LED enhanced the biomass of calli in Solanum xanthocarpum [38] and Lepidium sativum [39].…”
Section: Effect Of Leds On Callus Induction and Proliferationmentioning
confidence: 67%
See 1 more Smart Citation
“…Recent report by Hassanpour [34] found that red-blue LED treatment was beneficial for callus production and secondary metabolism in Hyoscyamus reticulatus. Similarly, the maximum callogenic biomass and high concentrations of bioactive compounds in Canavalia ensiformis were reported in mixed red-blue light treatment [35]. Moreover, white LED enhanced the biomass of calli in Solanum xanthocarpum [38] and Lepidium sativum [39].…”
Section: Effect Of Leds On Callus Induction and Proliferationmentioning
confidence: 67%
“…Similarly, Nhut true [37] also demonstrated that yellow light was beneficial for the proliferation of callus and higher biomass in Panax vietnamensis. Apart from the individual spectral qualities, the combination of two or more light qualities further improved the callus induction and proliferation in in vitro plant cultures [35]. Mixed red and blue LED was beneficial for callus proliferation.…”
Section: Effect Of Leds On Callus Induction and Proliferationmentioning
confidence: 96%